Marketing factors associated with a continuous positive airway pressure machine purchasing in patients with obstructive sleep apnea - Bundit Sawunyavisuth; Nattaporn Sopapol; Chi-Hsing Tseng; Kittisak Sawanyawisuth (Future Science OA, 2023)
Aim: Obstructive sleep apnea (OSA) is related with several cardiovascular diseases. It should be treated with a continuous positive airway pressure (CPAP) machine. There is limited data on marketing factors on a decision of CPAP machine purchasing in OSA patients. Materials & methods: We enrolled adult patients aged over 18 years with OSA who tried a CPAP. Marketing factors were evaluated for a decision of CPAP machine purchasing. Results: There were 95 OSA patients participated in the study. Nice color CPAP machine and good knowledge and informative salesperson had adjusted odds ratio (aOR) of 4.480 and 9.478, the other two factors had aOR at 0.102 and 0.217. Conclusion: Marketing factors related to CPAP machine purchasing in patients with OSA.